Oceanographic Data of the 22nd Japanese Antarctic Research Expedition from November 1980 to April 1981 - クラモト, シゲキ; コヤマ, カオル; KURAMOTO, Shigeki; KOYANA, Kaoru (National Institute of Polar Research, 1982)
P(論文) This report presents the data of the oceanographic observations on the icebreaker Fuji and the tidal observation at Syowa Station, which were carried out in the summer mission of the 22nd Japanese Antarctic Research Expedition in 1980-1981. departmental bulletin paper